Pemanfaatan Modal Nafkah Rumahtangga Petani Padi pada Masa Pandemi Covid-19 di Desa Pasirtalaga, Kecamatan Telagasari, Kabupaten Karawang. - Putri Cahyaning Ramadhan; Kuswarini Sulandjari; Suhaeni Suhaeni (Peneliti.net, 2022)
The Covid-19 pandemic has spread massively in various countries, including Indonesia. Various sectors of the national economy have experienced the impact of the Covid-19 pandemic, including the agricultural sector. During the Covid-19 pandemic, rice farmer households in Pasirtalaga Village used livelihood capital to protect their livelihoods from being vulnerable. The purpose of this study was to analyze the characteristics of rice farmers' households and identify the use of capital for rice farmers' households during the Covid-19 pandemic in Pasirtalaga Village, Telagasari District, Karawang Regency. Determination of the sample by a simple random sampling technique through the Slovin formula, totaling 35 respondents. The data in this study consisted of primary data and secondary data. Primary data collection was carried out in several ways, namely the distribution of questionnaires, interviews, and observations. Secondary data is collected by analyzing documents, such as theses, theses, books, journals, articles, and the internet that are related to this study. The data analysis technique used scoring, category, and descriptive analysis. The results of the research on the characteristics of farmer households in Pasirtalaga Village, the majority live at home, have a land tenure pattern of < 0.65 ha, have two livelihoods, and have more than 3 family members. The subsistence capital bases of lower-level households are natural capital, social capital and physical capital, all at level 3. The capital base for middle-class households is natural capital, human capital and financial capital, all at level 3. Capital base The upper layers of household income are human capital, physical capital and financial capital with each being at level 3.